Pendampingan Perencanaan dan Pengendalian Produksi di PT. Ganding Toolsindo - Annisa Dewi Akbari; Idriwal Mayusda; Tiena Gustina Amran; Nora Azmi; Sisca Dewi Septiani (Abdimas Universal, 2022)
Achieving production targets is the goal of all companies, especially manufacturing companies. PT Ganding Toolsindo is an automotive component manufacturing company that aims to provide a high level of service and is committed to its clients, so achieving production targets is essential. However, it is unfortunate that there are still problems regarding the non-fulfillment of production targets. In addition, issues regarding rusty raw materials and waste also occur there. The cause of this problem is the advantages and disadvantages of raw materials because production planning and control have not been appropriately implemented. Therefore, this Community Service (PkM) aims to assist partners in solving these problems through training, production planning, and control assistance. The PkM series is carried out with a preliminary survey, material preparation, training, and mentoring. The material given in this PkM activity is about "Introduction to Production Planning and Control" and "Production Planning and Control Systems for Make to Order (MTO) Type Companies.” In addition, assistance is provided to solve problems that are the company's focus, namely making Side Tube part products by making dual kanban for the parts. Based on the evaluation results, this PkM activity has been carried out well and received a positive response from PkM partners, namely PT. Ganding Toolsindo.